An Eco-friendly Degumming of Apocynum Venetum with Ionic Liquid Pretreatment. Issue 10 (2nd October 2020) - Yang, Fengrui; Ma, Yingchong; Zheng, Huanda; Zheng, Laijiu; Zhao, Yuping
ABSTRACT: A novel pretreatment process for degumming of apocynum venetum is developed firstly using 1-butyl-3-methylimidazolium acetate-water mixtures. The effect of the four independent parameters on the residue of gum of apocynum venetum fibers was investigated. The results showed that the effect of 1-butyl-3-methylimidazolium acetate concentration on the residue of gum is the most significant, followed by time, temperature, and liquor ratio. The optimal solution of ionic liquid pretreatment for the degumming of apocynum venetum fiber is obtained with a concentration of ionic liquid 80%, liquor ratio 1:20, temperature 90°C, and time 4 h. The residual gum contents for the chemical degummed apocynum venetum fibers were 3.90% with ionic liquid pretreatment. Moreover, the physicochemical properties of the degummed apocynum venetum fibers were also characterized by Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD) and Scanning electron spectroscopy (SEM).